PENGARUH ARUS KAS OPERASI TERHADAP PERTUMBUHAN LABA PERUSAHAAN PADA PT PEGADAIAN (PERSERO) KANWIL I MEDAN - Novien Rialdy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
AbstractThis research is to find out the influence of the operational cashflow and the profit growth at PT. Pegadaian (Persero) Kanwil I Medan. The methodology for the research are descriptive quantitative with quantitative data. The results is finding the significant influence of the operational cashflow and the profit growth at PT. Pegadaian (Persero) Kanwil I Medan. From determinant result that cashflow influence 52.6% to profit growth and from the hipotesis H there are significant influence variable X (operational cashflow) to variable Y(9rofit growth).Keywords : operational cashflow, profit growth